Mediation effect of psychological contract between personality dimensions and turnover intention - Saeed, Maryam (Universidad ESAN. ESAN Ediciones, 2020)
Purpose: This study aims to test the mediating role of psychological contract (PC) in a relationship between personality dimensions and turnover intention. Design/methodology/approach: The current study is analytical in nature. The data for the purpose of the analysis is collected from 300 software engineers working in Lahore, Punjab. Purposive sampling technique is used for the collection of this data. The response rate was 87.33 per cent. Different data analysis techniques such as correlation, regression analysis, are used to test the 10 hypotheses of the study. Moreover, the study adopted a cross-sectional survey design. Findings: According to regression analysis, extroversion, conscientiousness and agreeableness personality dimensions brought positive but insignificant increments in turnover intention. However, emotionally stable personality dimensions brought positive and significant increments in turnover intention. Open to experience personality dimension brought negative but insignificant decrement in turnover intention. Results showed extroversion personality dimension brought a very less but insignificant increment in variations of PC, which have higher contributions in variations of turnover intention. Emotional stable, conscientiousness and agreeableness personality dimensions brought also very less but a significant increment in PC. Open to experience personality dimension have negative but insignificant decrement in PC. Results showed the mediation impact of PC among emotional stability, conscientiousness and agreeableness personality dimensions and turnover intention. However, PC does not mediate among extroversion, open to experience personality dimensions and turnover intention. The paper concludes with recommendations for further research. Originality/value: This study will help the organization in reducing the turnover rate and can enhance the motivation level of their employees

Propósito: Este estudio tiene como objetivo probar el papel mediador del contrato psicológico (CP) en la relación entre las dimensiones de la personalidad y la intención de rotación. Diseño/metodología/enfoque: El presente estudio es de naturaleza analítica. Los datos para el análisis se recopilan de 300 ingenieros de software que trabajan en Lahore, Punjab. Para la recopilación de estos datos se utiliza una técnica de muestreo intencional. La tasa de respuesta fue del 87,33 por ciento. Se utilizan diferentes técnicas de análisis de datos, como correlación y análisis de regresión, para probar las 10 hipótesis del estudio. Además, el estudio adoptó un diseño de encuesta transversal. Hallazgos: Según el análisis de regresión, las dimensiones de personalidad extroversión, escrupulosidad y amabilidad produjeron incrementos positivos pero insignificantes en la intención de rotación. Sin embargo, las dimensiones de personalidad emocionalmente estables trajeron incrementos positivos y significativos en la intención de rotación. La dimensión de personalidad abierta a la experiencia trajo una disminución negativa pero insignificante en la intención de rotación. Los resultados mostraron que la dimensión de personalidad extrovertida produjo un incremento menor pero insignificante en las variaciones de CP, que tienen mayores contribuciones en las variaciones de la intención de rotación. Las dimensiones de personalidad estable emocional, escrupulosidad y amabilidad también trajeron un incremento muy menor pero significativo en la CP. La dimensión de personalidad abierta a la experiencia tiene una disminución negativa pero insignificante en la CP. Los resultados mostraron el impacto mediador de la CP entre las dimensiones de personalidad de estabilidad emocional, escrupulosidad y amabilidad y la intención de rotación. Sin embargo, la CP no media entre las dimensiones de personalidad extrovertida, abierta a la experiencia y la intención de rotación. El artículo concluye con recomendaciones para futuras investigaciones. Originalidad/valor: este estudio ayudará a la organización a reducir la tasa de rotación y puede mejorar el nivel de motivación de sus empleados.
Keywords: Extroversion personality dimension (EPD); Consciousness personality dimension (CPD); Dimensión de personalidad extrovertida (EPD); Agreeable personality dimension (APD); Dimensión de personalidad consciente (CPD); Openness to experience personality dimension (OEPD); Dimensión de personalidad agradable (APD); Dimensión de personalidad de apertura a la experiencia (OEPD); Psychological contract (PC); Contrato psicológico; https://purl.org/pe-repo/ocde/ford#5.02.04